The Association between Knowledge and Midwivery Education With Implementation Pap Smear in The Room of PONEK RSUD Siti Aisyah Kota Lubuklinggau - Mika Oktarina; Nuril Absari; Listra Afriani (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2019)
Still high maternal mortality caused by cervical cancer. This study aimed to study the relationship of knowledge and midwife investigation with the implementation of pap smear examination in Ponek Room of Siti Aisyah Hospital Lubuklinggau. This research was descriptive research, using cross sectional design. Population in this research was all midwife in Room Ponek Siti Aisyah Hospital Lubuklinggau with number 38 people. Technique of data retrieval in this research used Total Sampling and obtained sampel as many as 38 people. Data collected in this study using questionnaires. Data analysis technique done by univariate and bivariate analysis with Chi-Square test (c²). The results of this study were: (1) There were 50% of respondents did not do pap smears, (2) There were 71.1% respondents who were educated DI-DIII, (3) There were 39.5% knowledgeable enough. (4) There is a significant correlation between midwife knowledge and the implementation of pap smear examination in Ponek Room of Siti Aisyah Hospital of Lubuklinggau City with Category of weak relationship. (5) There is a significant correlation between midwife education and the implementation of pap smear examination in Ponek Room of Siti Aisyah Hospital of Lubuklinggau City with weak relationship category. It is expected that RSUD Siti Aisyah can improve service improvement and program improvement so that Pap smears are not only done in the morning so all the midwives get the same chance. Keywords: knowledge, midwivery education, pap smear examination